Pengaruh Ukuran Perusahaan, Profitabilitasdan Financial Leverage Terhadap Praktik Perataan Laba Pada Perusahaan Manufaktur - Nanda Ayunika, Ni Putu; Yadnyana, I Ketut (E-Jurnal Akuntansi, 2018)
This study aims to provide and empirical awareness of accounting students that is measured by the level of interest, knowledge, challenges, and benefits in influencing IFRS convergence. This research was conducted at six universities in Bali Province. The number of respondents totaling 282 students was selected using a purposive sampling technique with the criteria of respondents are accounting students in Higher Education and Private Universities in the VIII Conference area and have an active Bachelor of Accounting program, accounting students in semester V and VII and has taken and is studying the subject of Accounting Theory. Methods of data collection were conducted by survey method using questionnaire . Data analysis technique used is the Analysis of Multiple Linear Regression. The final result of the study states that the variable level of interest, knowledge, and benefits has a positive effect on awareness of IFRS convergence. While the level of challenge variable has a negative effect  towards IFRS convergence awareness. Keywords: Interest level, knowledge level, challenge level, benefit level, awareness of IFRS convergence